2020
DOI: 10.1007/s13592-020-00800-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding pollinator foraging behaviour and transition rates between flowers is important to maximize seed set in hybrid crops

Abstract: Hybrid cauliflower production predominately relies on pollen transfer from hermaphrodite to female lines by honeybees. However, the presence of other pollinators may impact pollination success. Here, we investigate how honeybee visitation frequency and behaviour vary with plant sex and presence of blowflies and affect seed and pod set. We found substantial pollen limitation when honeybees were alone. This was likely due to their higher visitation to hermaphrodite flowers, infrequent transition from hermaphrodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Ferguson) in Spain (Miñarro & Twizell 2015). Gagic et al (2021) also found that honeybees caused pollen limitation in cauliflower ( Brassica oleracea var. botrytis L.) due to their preferences for hermaphrodite flowers and their high nectar thievery.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ferguson) in Spain (Miñarro & Twizell 2015). Gagic et al (2021) also found that honeybees caused pollen limitation in cauliflower ( Brassica oleracea var. botrytis L.) due to their preferences for hermaphrodite flowers and their high nectar thievery.…”
Section: Introductionmentioning
confidence: 98%
“…Yet their importance is also a consequence of temporal and spatial change in abundance, the change of landscape structures at different scales and their foraging activity and behaviour (Mateos‐Fierro et al 2022; Saturni et al 2016). It is also generally assumed that high flower visitation rate by bees is a strong indicator of high pollination efficiency (Gagic et al 2021). However, given that some bee species may be inefficient in pollen transfer and some plants have physiological characteristics that require specialist pollinators, neither the abundance of floral visitors nor the rate of visits is equivalent to more successful pollination (Gagic et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of gynodioecy, a preference for one floral morph over another can result either from one sex being more attractive or rewarding than the other (Delph & Lively 1992;Ashman 2000), or a foraging preference for pollen-producing (Larsson 2005) or pollen-deficient flowers (Waller et al 1985). In agriculture, honey bees have shown a preference for hermaphroditic plants over malesterile ones in hybrid systems of Brassica napus (Mesquida & Renard 1981), carrot (Gaffney et al 2019), and cauliflower (Gagic et al 2021). Finally, spatial separation between patches of male and female flowers can result in pollinators individually specializing on a single morph.…”
Section: Introductionmentioning
confidence: 99%